Design and development of transient surge protection device for railway application - Doo, Yi Hui (Nanyang Technological University, 2021)
Lightning transient surge pose a serious threat to Singapore’s Railway Systems as it can results in service disruption and train electronic equipment’s damage. The current Singapore’s Railway systems are fitted with commercially available lightning surge protector however there are reported cases of train electronic equipment’s damage due to lightning [1]. The aim of this project is to design and develop a Transient Surge Protection Device (SPD) dedicated for Singapore lightning climate and Railway Application. To meet this aim, the project will study on the Lightning Protection Zone (LPZ) model for a typical train, existing surge protection design in the train and commercially available SPD circuits. The study will involve the transient surge circuit simulation on the SPD, to improvise the SPD circuit design and finally to develop a physical prototype SPD with in-house laboratory test to verify the circuit simulation.